Sacramento Valley Region of California Agricultural Teachers' Association Conference [copy negative] - Frank Aston::::::photographer::: (1938)
The Sacramento Valley Region of the California Agricultural Teachers' Association met at the California Polytechnic School for its annual conference, June 27-July 9, 1938.